A control system of elevators by using Programmable Logic Controller (PLC): article / Norshuhada Kamarudin - Kamarudin, Norshuhada (2006)
A low cost elevator control system has been developed by using Programmable Logic Controller (PLC). PLC is used as a controller for an elevator system that has two elevators with five floors. The PLC will control vertical movement of the two elevators either moving up or down simultaneously with only one PLC. The PLC also control opened and closed door process after the elevator had reached each level. The automation of this elevator process consists in providing technological means for its selective operation and control, such that the system as so conceived is enabled to deal with those situations for which a proper command has been implemented.